Effects of Intraoperative Dexamethasone and Ondansetron on Postoperative Nausea and Vomiting in Microvascular Decompression Surgery: A Randomized Controlled Study - Cattleya Thongrong; Patitha Chullabodhi; Pornthep Kasemsiri; Amnat Kitkhuandee; Narin Plailaharn; Lumyai Sabangban; Thirada Jimarsa (Anesthesiology Research and Practice)
Background. Postoperative nausea and vomiting (PONV) is a common problem and may lead to catastrophic complications, especially in neurosurgical cases. The aim of this study was to evaluate the effects of dexamethasone and ondansetron for preventing PONV in patients who underwent microvascular decompression (MVD) surgery. Methods. A prospective, double-blinded, randomized control trial was conducted with 54 patients who underwent MVD. Patients were allocated into two groups. The study group (Gr. D) received intraoperative dexamethasone 4 mg iv and ondansetron 4 mg iv, whereas the control group (Gr. N) received placebo (0.9% normal saline 1 ml iv and 0.9% normal saline 2 ml iv). The incidence and severity of PONV were observed at 1, 2, 4, and 24 hr postsurgery. Results. At 1, 2, 4, and 24 hr postsurgery, Gr. D had a lower incidence (7.4%, 11.1%, 29.6%, and 66.7%) and lower severity of PONV than Gr. N (18.5%, 29.6%, 37.0%, and 81.5% at 1, 2, 4, and 24 hr; p>0.05). The requirement for antiemetic drugs was not significantly different between the groups (p>0.05). Conclusion. Administration of dexamethasone and ondansetron 4 mg seemed to decrease the incidence of PONV in the first 24 hours but not significantly. Therefore, further studies are to be carried out by escalating either dexamethasone dose or the dose of ondansetron or both.